2016
DOI: 10.1371/journal.pone.0153790
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalized Patients at High Risk for Obstructive Sleep Apnea Have More Rapid Response System Events and Intervention Is Associated with Reduced Events

Abstract: BackgroundRapid response system (RRS) is a safety tool designed for early detection and intervention of a deteriorating patient on the general floor in the hospital. Obstructive sleep apnea (OSA) has been associated with significant cardiovascular complications. We hypothesized that patients with high-risk of OSA have higher rate of RRS events and intervention with positive airway pressure therapy in these patients can mitigate the RRS events.MethodsAs part of a clinical pathway, during a 15 month period, pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
(27 reference statements)
0
13
0
2
Order By: Relevance
“…Consequently, evidence to guide the management of cardiac inpatients with OSA is limited. Previous studies have highlighted that cardiac inpatients with a high risk of OSA are more likely to experience critical events requiring activation of rapid response systems [12,13]. Treatments such as positive airway pressure (PAP) therapy can potentially reduce critical events, which have several implications for clinical practice [12].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, evidence to guide the management of cardiac inpatients with OSA is limited. Previous studies have highlighted that cardiac inpatients with a high risk of OSA are more likely to experience critical events requiring activation of rapid response systems [12,13]. Treatments such as positive airway pressure (PAP) therapy can potentially reduce critical events, which have several implications for clinical practice [12].…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis and treatment is essential to decrease the impact of OSAS in the quality of life of patients [2].…”
Section: Introductionmentioning
confidence: 99%
“…Early recognition of highrisk patients for obstructive sleep apnea in hospitalized patients also predicted more frequent rapid response events, which were reduced in patients who were successfully intervened with PAP therapy. 9 The major finding in this study was that patients treated and compliant with PAP therapy showed a significant survival advantage compared with those who were noncompliant. We do not believe that differences in various comorbidities explains the observed survival advantage of PAP therapy-adherent patients in that there were few differences in the prevalence of important comorbid conditions between the 2 groups, and this observation was supported using an inverse propensity score analysis that accounted for differences between the 2 groups.…”
Section: Discussionmentioning
confidence: 70%
“…Of 5062 patients included in the final database, 1161 patients have been included in prior publications. 9,11,12,16,17 The Thomas Jefferson University Institutional Review Board approved the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation